Protein folds and IV structure - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Multiple-folds, Stable quaternary structure, Transient quaternary structure, Binding/Interaction domains, Levels of protein structure
Reviewed at 2022/11/27